2016
DOI: 10.1007/s10517-016-3240-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficiency of Adeprophen and Antidepressants of Various Groups on the Model of Reserpine-Induced Depression in Rats

Abstract: A new (aryloxyalkyl)adenine derivative Adeprophen (9-[2-(4-isopropylphenoxy)ethyl]adenine, VMA-99-82) has a strong antidepressant effect on the model of reserpine-induced depression in rats (single dose 4 mg/kg, intraperitoneally). This effect manifested in suppression of depression-like behavior in the Porsolt forced swimming test (shortening of immobility time and increase in immobility latency, number of jumping episodes, and time of active swimming) and sucrose consumption/preference test (increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…Adolescent substance users show abnormalities in neurocognition, brain structure and brain function. 43 The findings of the present study showed that abuse of tramadol or cannabis alone caused antidepressant-like behaviour, impaired spatial memory, elevated 5-HT levels in the cerebral cortex and hippocampus, induced oxidative stress and apoptosis in brain tissue and deleteriously altered brain structure. Tramadol abuse had a potent antidepressant effect and a more potential to elicit oxidant stress than cannabis.…”
Section: Discussionsupporting
confidence: 46%
“…Adolescent substance users show abnormalities in neurocognition, brain structure and brain function. 43 The findings of the present study showed that abuse of tramadol or cannabis alone caused antidepressant-like behaviour, impaired spatial memory, elevated 5-HT levels in the cerebral cortex and hippocampus, induced oxidative stress and apoptosis in brain tissue and deleteriously altered brain structure. Tramadol abuse had a potent antidepressant effect and a more potential to elicit oxidant stress than cannabis.…”
Section: Discussionsupporting
confidence: 46%
“…Studies have found that reserpine is widely used in the modeling of depression, Parkinson's disease and schizophrenia (Fernandes et al, 2012;Park et al, 2018). The reserpine-induced depression rat model can be divided into two types, one for a low dose (i.p., 0.1-0.5 mg/kg) and one for a single high dose (i.p., 1-5 mg/kg) (Fernandes et al, 2012;Ozerov et al, 2016). According to the pre-experiment, a single dose of 4.0 mg/ kg reserpine induced depressive symptoms in model rats and was significantly more effective than a single dose of 0.3 mg/kg of reserpine; for example, to decrease the exercise activity in the OFT, to increase the exercise time in the FST and to reduce the sugar water preference in the SPT.…”
Section: Discussionmentioning
confidence: 98%
“…Results of the 5HTP test support that FCS-304 could act through a pro-serotoninergic mechanism at the central level. In addition, given that forced swimming and reserpine tests are high sensitive to non-selective agents, among them, tricyclic antidepressants (32,33), it is reasonable to assume that imipramine shows a greater response in both assays, whereas FCS-304 is more effective against 5-HTP.…”
Section: Discussionmentioning
confidence: 99%